1994
DOI: 10.1007/bf01310568
|View full text |Cite
|
Sign up to set email alerts
|

Specific detection of positive and negative stranded hepatitis C viral RNA using chemical RNA modification

Abstract: Since hepatitis C virus (HCV), a major causative agent of posttransfusional non-A, non-B hepatitis, is a positive stranded RNA virus, it is supposed to replicate via a negative RNA strand. Although strand specific reverse transcription-polymerase chain reaction (RT-PCR) method was recently developed to detect each strand of HCV RNA, the specificity of the strategy has remained to be determined. In this study, using in vitro transcribed positive and negative stranded HCV RNAs mixed with hepatic cellular RNA fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
56
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 17 publications
2
56
0
Order By: Relevance
“…In addition, an RT reaction was carried out in the absence of the antisense primer with Superscript II after chemical modification of RNA to analyze the specificity of negative-stranded HCV RNA. 32 RT reaction was conducted by use of the primer La3 (for positive-stranded RNA) and primer Ls1 (for negative-stranded RNA) (Fig. 2A).…”
Section: Determination Of the 3ј Extra Sequence In The Plasma Of Donomentioning
confidence: 99%
“…In addition, an RT reaction was carried out in the absence of the antisense primer with Superscript II after chemical modification of RNA to analyze the specificity of negative-stranded HCV RNA. 32 RT reaction was conducted by use of the primer La3 (for positive-stranded RNA) and primer Ls1 (for negative-stranded RNA) (Fig. 2A).…”
Section: Determination Of the 3ј Extra Sequence In The Plasma Of Donomentioning
confidence: 99%
“…Positive-strand HCV RNA has indeed been detected by reverse-transcription polymerase chain reaction (RT-PCR) in peripheral blood mononuclear cells (PBMC) in several studies investigating patients at various stages of the viral infection. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] Furthermore, it was possible in some cases to detect the negative strand of HCV RNA, and thus to suggest that HCV RNA might replicate in these cells. [11][12][13][14][15][16][17][18][19][20][21] These findings were further substantiated by the detection of HCV genomes in PBMC and liver mononuclear cells by using in situ hybridization.…”
mentioning
confidence: 99%
“…Several investigators have now emphasized the risk of false-positive results when detecting negative HCV-RNA strands by PCR. 20,21,[24][25][26] Moreover, detection of HCV-RNA positive strands cannot be taken as firm evidence of PBMC infection because of the obvious risk of viral particle adsorption into mononuclear blood cells. We have therefore hypothesized that using the severe combined immunodeficiency (SCID) mouse model 27 might be of value to clarify some of these issues for the following reason: It has been demonstrated that this model allows long-term survival of human hematopoietic cells.…”
mentioning
confidence: 99%
“…The primer-dependent mechanism for RT reaction has been generally accepted over the years. However, during RT-PCR analysis of human and animal RNA viruses, bacterial operons, as well as eukaryotic cellular RNAs, it has been observed that cDNA could be synthesized by reverse transcriptase without the addition of exogenous oligonucleotide (Gunji et al, 1994;Lanford et al, 1995;Lerat et al, 1996;Schoenike et al, 1999;Guacucano et al, 2000;Peyrefitte et al, 2003;Haddad et al, 2007;Tuiskunen et al, 2010, Moison et al, 2011. This completely contradicts the well-accepted mechanism of cDNA synthesis, indicating that RT occurs in a primer-independent manner.…”
mentioning
confidence: 52%
“…However, many lines of evidence supported the possibility that this kind of cDNA synthesis is most likely primed by cellular small nucleic acids (DNA, microRNA, tRNA, etc. ) associated with the commercial reverse transcriptase as well as template RNA, or by the thermosTable hairpin structure at the 3'-end of the template RNA, the so called self-priming (Agranovsky, 1992;Gunji et al, 1994;Lerat et al, 1996;Timofeeva and Skrypina, 2001;Piche and Schernthaner, 2003;Haddad et al, 2007;Tuiskunen et al, 2010;Moison et al, 2011). Regardless, since the primer-independent RT usually contributes to non-specific cDNA synthesis that may interfere with the PCR specificity, thus resulting in misinterpretation of the final experimental data, much effort has been devoted to overcoming this unexpected event (Lerat et al, 1996;Peyrefitte et al, 2003;Haddad et al, 2007;Moison et al, 2011).…”
mentioning
confidence: 99%